Economic efficiency of vibroreinforced soil-cement piles implemented in construction (Academic journal Industrial Machine Building Civil Engineering, 2018)
The results of the executed economic comparison of foil-cement piles reinforcement use by vibroreinforced - vibroreinforced soil-cement piles are presented. The comparison is based on the results of piles bearing capacity by field tests. Considering the results of field tests two variants of piles foundation have been designed for residential building. Economical comparison is made for implementation effectiveness of reinforced and non-reinforced soil-cement piles at the piles calculated bearing capacity on the soil that is greater than the calculated bearing capacity by the material. .Economical comparison is made for implementation effectiveness of vibrated vibroreinforced soil-cement piles and bored piles at their calculated bearing capacity by the material at times greater than that on the soil. The obtained results and the determined economic effect are analyzed. The results of comparison are used for design and implemented in construction.
Keywords: the vibroreinforced soil-cement piles; economic efficiency; deep soil mixing method; the bored piles